Interpreting the National Electrical Code - Truman C. Surbrook (Thomson Delmar Learning, 2005)
This updated text provides a process for understanding and applying the National Electrical Code to electrical contracting, plan development and review. Based on the 1999 Code, which has undergone major revisions, this text covers practical problems and questions from every article of the Code, including numerous examples involving residential, commercial, agricultural and industrial installations. The logical presentation of the Code should help instructors to teach the material